The Trends of Digital Da’wah: Cyber Media Analysis on Instagram Account - Khotimah, Nurul; Kamila, Fitri Shafa (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
The transformation of da'wah from time to time has entered the joints of technology. Da'wah, primarily conducted face-to-face, has now turned digital, especially through social media such as Instagram. @Ngajikyaigusbaha is an Instagram account that engages in da'wah activities through videos. The contents are delivered using video compilations of da'wah by Gus Baha. They are conveyed in an attractive and straightforward visual presentation, making it easier and more understandable for the audience. This research's objective is to find out and analyze the forms of digital da'wah trends on the @ngajikyaigusbaha account. This research data was collected from virtual interviews, observation, and documentation. The data were analyzed using cyber media analysis, including four unit levels; media space, media archive, media object, and experience. The results showed the digital da'wah trend on the @ngajikyaigusbaha account at each level as follows: 1) The media space level; the da'wah adopted the preaching of Gus Baha and gained 93,6 thousand followers. 2) The media document level; the content contains the real-life phenomenon within society in videos, either in video recordings or attractive visuals, up to 3-4 contents in a day covering messages of aqidah, morality, and syariah. 3) Media object level; there are interactions between users and admins. 4) Media experience level; the uploaded contents are relevant to real life and experienced by almost all followers.